Research on the privacy-preserving point-in-polygon protocol - Jing ZHANG; Shou-shan LUO; Yi-xian YANG; Yang XIN (Tongxin xuebao)
A privacy-preserving point-in-polygon protocol was proposed under semi-honest model, to deal with the prob-lem of high complexity and limitation of the existing protocols. First, an blivious point-line protocol was designed by extending the traditional point-line protocol, making the use of 1-out-n oblivious transfer and the geometric properties of the vector. Then, based on this protocol and combined with the secure binary search protocol, the final solution was put forward. The security of the protocol was proved with ich method. Meanwihle, the validity and the complexity of the protocol were also be analyzed. It is shown that this new protocol gets the advantage over the existing one in terms of efficiency and enjoys excellent expandability.